Review Pemanfataan Data Electroencephalogram (EEG) dengan metode Convolution Neural Network - Muchamad Kurniawan; Andy Rachman; Adib Pakarbudi (INTEGER: Journal of Information Technology, 2021)
Electroencephalogram (EEG) is a brain data signal that is captured by sensors. Many studies have used EEG to be used as a decision maker or classifying. What classification has been used most frequently in existing studies over the last 5 years? These are the questions that will be answered in this research. In addition to these questions, another question that will be answered is what is the most popular method used in processing EEG data? The final question in research is the recent development of EEG and CNN research. The results of these answers are the most popular research using the CNN method as a classification method, the application of the field of Human-computer InterfacesKeywords: Electroencephalogram, Convolution Neural Network.